When the skeletons escape the closet :managing the monsters in Izinyoka/Snakes - Stoykov, Stanimir (My University, 2019)
This dissertation aims to critically examine the Mzansi Bioskop formula for story-telling, prescribed by the DSTV channel, and highlight its problematic nature in terms of predictable narratives which could arguably perpetuate negative societal stereotypes of women, children, and the queer community. This research combines a written dissertation and the production of the short film Izinyoka/Snakes (2018), which examines the Mzansi Bioskop channel melodrama formula of current South African made-for-television film-making practices. The dissertation further compares case studies like Mandla N’s productions Plastic Money (2014) and Jozi to Kapa (2013) in order to analyse the impact of the formulaic approaches to cinematic representation. This dissertation and the film Izinyoka/Snakes (2018) propose the possibility and value of these film-making practices being used to construct a “camp” and satirical film-narrative and aesthetic, which ultimately provides avenues for exploring a world which exists beneath and alongside the surface of predictable genre formulations, narrative styles, and character relations that are currently pursued by the channel. This position is debated through the reading of historic film genres and concepts and their adaptation to the South African popular film formulae.
A Dissertation submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Film and Television, 2019
Keywords: Melodrama; Motion pictures